Ring 20 chromosome phenotype. Issue 6 (June 1987) - Porfirio, B; Valorani, M G; Giannotti, A; Sabetta, G; Dallapiccola, B
Abstract : A baby with a 46, XY, r(20) karyotype is described. The distinguishing features of this rare chromosome anomaly are analysed in the light of the suggested r(20) syndrome.